1993
DOI: 10.1007/s0054030070075
|View full text |Cite
|
Sign up to set email alerts
|

Strain-differences of sensitivity to volatile anesthetics and their genetic character in mice

Abstract: Using loss of the righting reflex, we determined the ED50 values for enflurane, isoflurane, sevoflurane and halothane in white-haired ddN mice and black-haired C57BL mice. The ED50s (Mean +/- SEM) in ddN and C57BL mice for enflurane were 1.65 +/- 0.01 and 1.19 +/- 0.01% atm, for isoflurane 1.02 +/- 0.01 and 0.74 +/- 0.01% atm, for sevoflurane 2.29 +/- 0.03 and 1.95 +/- 0.03% atm, and for halothane 0.97 +/- 0.01 and 0.97 +/- 0.01% atm, respectively. The results indicate that the ddN strain is more resistant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Different mouse strains have been found to display different sensitivities to anesthetics (42). Moreover, the inflammatory responses induced by LPS also differ among various mouse strains (17).…”
Section: Resultsmentioning
confidence: 99%
“…Different mouse strains have been found to display different sensitivities to anesthetics (42). Moreover, the inflammatory responses induced by LPS also differ among various mouse strains (17).…”
Section: Resultsmentioning
confidence: 99%
“…strains of male mice, ddN, C57BL/6J, and MSM, were used. Tanaka et al reported that the ddN mouse was more resistant to three volatile anesthetics than the C57BL/6J mouse [1]. We decided to measure the enflurane requirement, because in enflurane, especially, the effective dose 50% (ED 50 ) values differed about 40% in this report, and because enflurane is more effective in the order of anesthetic sensitivity.…”
Section: Introductionmentioning
confidence: 94%
“…This part includes the midbrain reticular formation activating system connected with consciousness. Tanaka et al have reported that there are 20 to 30 cooperative factors in anesthesia, based on the anesthetic dose-LORR relation, including catecholamines [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloned genes are useful for elucidating diseases in molecular biological terms and are helping to increase the understanding of hereditary and incurable diseases. Sensitivity to anesthetics is also considered to be governed by genes, because many mutants with heritable altered sensitivities to general anesthetics have been isolated and analyzed in Drosophila melanogaster [4,5] and C. elegans [6] strains, as well as mouse strains [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%